A ceramic brazing vacuum electrical connector and a preparation method thereof
By using composite brazing materials containing Ti(C,N)-based cermet material for ceramic brazing, the problem of high residual stress after brazing in vacuum electrical connectors is solved, and high-strength plug-and-pull connections and high-strength brazing joints are realized.
Patent Information
- Application Number
- CN202411336422.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing ceramic brazed vacuum electrical connectors have high residual stress after brazing, which affects their mechanical properties and makes it difficult to achieve high-strength plug-and-removal connections.
The conductive metal core rod is welded with the ceramic insulator and vacuum flange by pressing and sintering of five layers of materials. The intermediate layer is a Ti(C,N)-based metal cermet layer, the surface layer is a Ti-Zr-Cu-Ni layer, and a Ti-Ni transition layer is arranged between the intermediate layer and the surface layer.
Reduces residual stress of the brazed joint, improves the mechanical properties of the vacuum electrical connector, supports high-strength plug-and-removal connections, and ensures that the brazed joint has high strength and good wettability.
Smart Images

Figure CN118867729B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic brazing, in particular to a ceramic brazing vacuum electric connector and a preparation method thereof. Background Art
[0002] Vacuum electrical connectors can transmit current, voltage or signals to or from a vacuum chamber. Vacuum electrical connectors generally include one or more metal conductors, each of which is surrounded by an insulator to insulate it from the vacuum chamber wall; the insulator is generally made of glass or ceramic material. Sealing is achieved by sintering glass and metal, and it has good high temperature resistance and corrosion resistance, but glass has poor thermal shock resistance and radiation resistance, and will anneal and soften, making it difficult to maintain sufficient rigidity to support high-strength plug-in connections. Therefore, ceramics are widely used as insulating materials in electrical connectors.
[0003] Due to the mismatch between the thermal expansion coefficient and elastic modulus of ceramics and metals, the difference in the chemical bond structure between ceramic materials and metal materials, and the special physical and chemical properties of ceramics themselves, it is difficult to achieve effective and reliable connection between ceramic insulating materials and metal conductors in electrical connectors by conventional fusion welding. Generally, brazing is used to connect ceramics and metals through Ag-based, Ti-based and other active brazing materials, which has the advantages of reliable joints, good repeatability, high production efficiency, etc. For example, a ceramic brazing connector and its preparation method disclosed in the patent with publication number CN117199888A improves the connector's high temperature resistance, radiation resistance, fire resistance, and heat shock resistance by brazing the pin, insulator, and shell as a whole.
[0004] When active solder is used for brazing, although the active solder has good wettability and airtightness, the thermal expansion coefficient between the ceramic material and the solder is quite different, resulting in high residual stress inside the electrical connector after brazing, thereby affecting the mechanical properties of the electrical connector and being unfavorable for high-strength plug-in connection of the vacuum electrical connector. Summary of the invention
[0005] The present invention aims to overcome the above-mentioned problems existing in vacuum electrical connectors in the prior art and provides a ceramic brazing vacuum electrical connector and a preparation method thereof. A conductive metal core rod is welded to a ceramic insulating part and a vacuum flange by a composite brazing material comprising a Ti(C,N)-based metal ceramic material, thereby reducing the residual stress of the brazing joint, improving the mechanical properties of the vacuum electrical connector, and facilitating high-strength plug-in connection.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A ceramic brazing vacuum electrical connector comprises a metal core rod, a ceramic insulating member and a vacuum flange sleeved outside the metal core rod; two ends of the ceramic insulating member are respectively welded to the metal core rod and the vacuum flange through a composite brazing material; a clearance fit is provided between the vacuum flange and the metal core rod;
[0008] The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C, N)-based metal ceramic middle layer, a Ti-Ni transition layer arranged on both sides of the Ti(C, N)-based metal ceramic middle layer, and a Ti-Zr-Cu-Ni layer arranged outside the Ti-Ni transition layers on both sides;
[0009] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 30-50:10:5-10:30-35:15-20:1-2;
[0010] The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 50-70:50-30;
[0011] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 55-60:10-15:15:15-25.
[0012] In the vacuum electrical connector of the present invention, the conductive metal core rod is welded to the ceramic insulating part and the vacuum flange for external connection by means of a composite solder comprising a Ti(C, N)-based metal ceramic material. The composite solder of the present invention is made by pressing and sintering five layers of materials, wherein the middle layer is a Ti(C, N)-based metal ceramic layer. The introduction of the Ti(C, N)-based metal ceramic material can reduce the thermal expansion coefficient of the brazing seam, realize the gradient transition of the thermal expansion coefficient between the metal core rod and the ceramic insulating part, and reduce the residual stress of the brazed joint, thereby improving the mechanical properties of the vacuum electrical connector and facilitating high-strength plug-in connection. The surface layer is a Ti-Zr-Cu-Ni layer, which enables the composite solder to have good wettability to the ceramic insulating part and can achieve good connection with the metal core rod, thereby ensuring that the brazed joint has high strength. At the same time, the present invention sets a Ti-Ni transition layer between the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Zr-Cu-Ni layer, which can achieve a good transition between the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Zr-Cu-Ni layer, and avoid the diffusion and flow of the liquid phase during the sintering process. The present invention controls the ratio of the hard phase TiC, TiN, Mo2C and the bonding phase Ni, Mo in the intermediate layer and the element type and dosage ratio of the transition layer, so that the Ti(C,N)-based metal ceramic layer and the Ti-Zr-Cu-Ni layer can be effectively transitionally connected, which is beneficial to improving the mechanical properties of the vacuum electrical connector.
[0013] Preferably, the particle size of nickel powder, titanium powder, molybdenum powder, zirconium powder, copper powder and carbon powder is 2-5 μm; the particle size of TiC powder, TiN powder and Mo2C powder is 0.5-1 μm.
[0014] Preferably, the thickness of the Ti(C,N)-based metal ceramic intermediate layer in the composite solder is 200-500 μm, the thickness of the two Ti-Ni transition layers is 20-50 μm, and the thickness of the two Ti-Zr-Cu-Ni layers is 100-200 μm.
[0015] Preferably, the ceramic insulating member is one of Al2O3 ceramic, SiC ceramic and Si3N4 ceramic.
[0016] Preferably, the metal core rod is one of copper and its alloys, stainless steel, aluminum and its alloys.
[0017] Preferably, the vacuum flange is a CF flange.
[0018] The present invention also discloses a method for preparing the ceramic brazing vacuum electrical connector, comprising the following steps:
[0019] (1) Preparation of composite solder:
[0020] A) respectively mixing the raw materials of the Ti(C,N)-based metal ceramic intermediate layer, the Ti-Ni transition layer and the Ti-Zr-Cu-Ni layer with a forming agent to obtain slurries of each layer;
[0021] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body;
[0022] C) vacuum sintering the green body to obtain a composite brazing material;
[0023] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0024] (3) After vacuum brazing, the ceramic brazed vacuum electrical connector is obtained.
[0025] Preferably, the molding agent in step A) is selected from one of polyethylene glycol, liquid paraffin, polyvinyl alcohol and glycerol; the mass of the molding agent is 5-10% of the mass of the slurry.
[0026] Preferably, the pressure during pressing in step B) is 100-200 MPa.
[0027] Preferably, the sintering temperature in step C) is 1400-1500° C., and the sintering time is 1-2 hours.
[0028] Preferably, the temperature during vacuum brazing in step (3) is 850-950°C, and the vacuum degree is 8.0×10 -3 Below Pa.
[0029] Therefore, the present invention has the following beneficial effects:
[0030] (1) Introducing Ti(C,N)-based metal ceramic materials into the composite solder can reduce the thermal expansion coefficient of the solder joint, achieve a gradient transition of the thermal expansion coefficient between the metal core rod and the ceramic insulating part, and reduce the residual stress of the solder joint, thereby improving the mechanical properties of the vacuum electrical connector and facilitating high-strength plug-in connection;
[0031] (2) The surface layer of the composite brazing material is a Ti-Zr-Cu-Ni layer, which enables the composite brazing material to have good wettability to the ceramic insulating part and can achieve good connection with the metal core rod, ensuring that the brazed joint has high strength;
[0032] (3) A Ti-Ni transition layer is set between the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Zr-Cu-Ni layer of the composite solder, which can achieve a good transition between the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Zr-Cu-Ni layer and avoid the diffusion and flow of the liquid phase during the sintering process from affecting the performance of the Ti(C,N)-based metal ceramic layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a cross-sectional view of the ceramic brazing vacuum electrical connector of the present invention.
[0034] In the figure: 1-metal core rod, 2-ceramic insulation, 3-vacuum flange, 4-composite solder. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0036] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0037] Overall embodiment:
[0038] A ceramic brazing vacuum electrical connector, such as Figure 1 As shown, it comprises a metal core rod 1, and a ceramic insulating part 2 and a vacuum flange 3 which are sleeved outside the metal core rod; two ends of the ceramic insulating part are respectively welded to the metal core rod and the vacuum flange through a composite brazing material 4; and a clearance fit is formed between the vacuum flange and the metal core rod;
[0039] The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C, N)-based metal ceramic middle layer, a Ti-Ni transition layer arranged on both sides of the Ti(C, N)-based metal ceramic middle layer, and a Ti-Zr-Cu-Ni layer arranged outside the Ti-Ni transition layers on both sides;
[0040] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 30-50:10:5-10:30-35:15-20:1-2;
[0041] The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 50-70:50-30;
[0042] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 55-60:10-15:15:15-25.
[0043] As a specific implementation, the particle size of nickel powder, titanium powder, molybdenum powder, zirconium powder, copper powder, and carbon powder is 2-5 μm; the particle size of TiC powder, TiN powder, and Mo2C powder is 0.5-1 μm.
[0044] As a specific implementation method, the thickness of the Ti(C,N)-based metal ceramic intermediate layer in the composite solder is 200~500μm, the thickness of the two Ti-Ni transition layers is 20~50μm, and the thickness of the two Ti-Zr-Cu-Ni layers is 100~200μm.
[0045] As a specific implementation, the ceramic insulating member is one of Al2O3 ceramic, SiC ceramic, and Si3N4 ceramic.
[0046] As a specific implementation, the metal core rod is one of copper and its alloys, stainless steel, aluminum and its alloys.
[0047] As a specific implementation, the vacuum flange is a CF flange.
[0048] The present invention also discloses a method for preparing the ceramic brazing vacuum electrical connector, comprising the following steps:
[0049] (1) Preparation of composite solder:
[0050] A) respectively mixing the raw materials of the Ti(C,N)-based metal ceramic intermediate layer, the Ti-Ni transition layer and the Ti-Zr-Cu-Ni layer with a forming agent to obtain slurries of each layer;
[0051] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body;
[0052] C) vacuum sintering the green body to obtain a composite brazing material;
[0053] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0054] (3) After vacuum brazing, the ceramic brazed vacuum electrical connector is obtained.
[0055] As a specific implementation, the molding agent described in step A) is selected from one of polyethylene glycol, liquid paraffin, polyvinyl alcohol, and glycerol; the mass of the molding agent is 5-10% of the mass of the slurry.
[0056] As a specific implementation, the pressure during pressing in step B) is 100-200 MPa.
[0057] As a specific implementation, the sintering temperature in step C) is 1400-1500° C., and the sintering time is 1-2 hours.
[0058] As a specific embodiment, the temperature during vacuum brazing in step (3) is 850-950°C, and the vacuum degree is 8.0×10 -3 Below Pa.
[0059] Embodiment 1:
[0060] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through a composite brazing material; the CF flange and the brass core rod are clearance-matched;
[0061] The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C,N)-based metal ceramic intermediate layer with a thickness of 300 μm, a Ti-Ni transition layer with a thickness of 30 μm arranged on both sides of the Ti(C,N)-based metal ceramic intermediate layer, and a Ti-Zr-Cu-Ni layer with a thickness of 150 μm arranged outside the Ti-Ni transition layers on both sides;
[0062] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 40:10:6:33:18:1.5;
[0063] The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 60:40;
[0064] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 58:12:15:20.
[0065] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0066] (1) Preparation of composite solder:
[0067] A) respectively mixing the raw materials of Ti(C,N)-based metal ceramic intermediate layer, Ti-Ni transition layer and Ti-Zr-Cu-Ni layer with polyethylene glycol (PEG6000) to obtain slurries of each layer; the mass of polyethylene glycol is 5% of the mass of the slurry;
[0068] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body at a pressure of 150 MPa;
[0069] C) vacuum sintering the green body to obtain a composite brazing material; the sintering temperature is 1440°C and the sintering time is 1h;
[0070] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0071] (3) At a temperature of 900°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0072] Embodiment 2:
[0073] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through a composite brazing material; the CF flange and the brass core rod are clearance-matched;
[0074] The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C,N)-based metal ceramic intermediate layer with a thickness of 200 μm, a Ti-Ni transition layer with a thickness of 20 μm arranged on both sides of the Ti(C,N)-based metal ceramic intermediate layer, and a Ti-Zr-Cu-Ni layer with a thickness of 100 μm arranged outside the Ti-Ni transition layers on both sides;
[0075] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 30:10:5:30:15:1;
[0076] The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 50:50;
[0077] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 55:10:15:15.
[0078] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0079] (1) Preparation of composite solder:
[0080] A) respectively mixing the raw materials of Ti(C,N)-based metal ceramic intermediate layer, Ti-Ni transition layer and Ti-Zr-Cu-Ni layer with polyethylene glycol (PEG6000) to obtain slurries of each layer; the mass of polyethylene glycol is 5% of the mass of the slurry;
[0081] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body at a pressure of 150 MPa;
[0082] C) vacuum sintering the green body to obtain a composite brazing material; the sintering temperature is 1400°C and the sintering time is 2h;
[0083] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0084] (3) At a temperature of 850°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0085] Embodiment 3:
[0086] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through a composite brazing material; the CF flange and the brass core rod are clearance-matched;
[0087] The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C,N)-based metal ceramic intermediate layer with a thickness of 500 μm, a Ti-Ni transition layer with a thickness of 50 μm arranged on both sides of the Ti(C,N)-based metal ceramic intermediate layer, and a Ti-Zr-Cu-Ni layer with a thickness of 200 μm arranged outside the Ti-Ni transition layers on both sides;
[0088] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 50:10:10:35:20:2;
[0089] The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 70:30;
[0090] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 60:15:15:25.
[0091] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0092] (1) Preparation of composite solder:
[0093] A) respectively mixing the raw materials of Ti(C,N)-based metal ceramic intermediate layer, Ti-Ni transition layer and Ti-Zr-Cu-Ni layer with polyethylene glycol (PEG6000) to obtain slurries of each layer; the mass of polyethylene glycol is 5% of the mass of the slurry;
[0094] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body at a pressure of 150 MPa;
[0095] C) vacuum sintering the green body to obtain a composite brazing material; the sintering temperature is 1500°C and the sintering time is 1h;
[0096] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0097] (3) At a temperature of 900°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0098] Comparative Example 1 (brazing with Ti-Zr-Cu-Ni solder):
[0099] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through Ti-Zr-Cu-Ni brazing filler metal; the CF flange and the brass core rod are clearance-matched;
[0100] The thickness of the Ti-Zr-Cu-Ni solder is 500 μm, and the raw materials include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 58:12:15:20.
[0101] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0102] (1) Preparation of Ti-Zr-Cu-Ni solder:
[0103] A) The raw materials of Ti-Zr-Cu-Ni solder are mixed evenly with polyethylene glycol (PEG6000) to obtain a slurry; the mass of the polyethylene glycol is 5% of the mass of the slurry;
[0104] B) coating the slurry on the inner surface of the mold and then pressing it into a green body at a pressure of 150 MPa;
[0105] C) vacuum sintering the green body to obtain Ti-Zr-Cu-Ni brazing filler metal; the sintering temperature is 1440°C and the sintering time is 1h;
[0106] (2) Assemble the ceramic insulator and the vacuum flange with the metal core rod, and place the Ti-Zr-Cu-Ni brazing filler metal at the welding position between the ceramic insulator and the vacuum flange and the metal core rod;
[0107] (3) At a temperature of 900°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0108] Comparative Example 2 (composite solder without Ti-Zr-Cu-Ni layer):
[0109] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through a composite brazing material; the CF flange and the brass core rod are clearance-matched;
[0110] The composite brazing material is made by pressing and sintering three layers of materials, wherein the three layers of materials include a Ti(C, N)-based metal ceramic middle layer with a thickness of 300 μm and a Ti-Ni layer with a thickness of 150 μm arranged on both sides of the Ti(C, N)-based metal ceramic middle layer;
[0111] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 40:10:6:33:18:1.5;
[0112] The raw materials of the Ti-Ni layer include nickel powder and titanium powder in a mass ratio of 60:40.
[0113] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0114] (1) Preparation of composite solder:
[0115] A) The raw materials of the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Ni layer are mixed evenly with polyethylene glycol (PEG6000) to obtain slurries of each layer; the mass of the polyethylene glycol is 5% of the mass of the slurry;
[0116] B) sequentially coating the inner surface of the mold with a Ti-Ni layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, and a Ti-Ni layer slurry, and then pressing the mold into a green body at a pressure of 150 MPa;
[0117] C) vacuum sintering the green body to obtain a composite brazing material; the sintering temperature is 1440°C and the sintering time is 1h;
[0118] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0119] (3) At a temperature of 900°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0120] Comparative Example 3 (composite solder without Ti-Ni transition layer):
[0121] A ceramic brazing vacuum electrical connector comprises a brass core rod and a SiC ceramic insulator and a CF flange sleeved outside the brass core rod; two ends of the SiC ceramic insulator are respectively welded to the brass core rod and the CF flange through a composite brazing material; the CF flange and the brass core rod are clearance-matched;
[0122] The composite brazing material is made by pressing and sintering three layers of materials, wherein the three layers of materials include a Ti(C, N)-based metal ceramic middle layer with a thickness of 300 μm and a Ti-Zr-Cu-Ni layer with a thickness of 150 μm arranged on both sides of the Ti(C, N)-based metal ceramic middle layer;
[0123] The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 40:10:6:33:18:1.5;
[0124] The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 58:12:15:20.
[0125] The method for preparing the ceramic brazing vacuum electrical connector comprises the following steps:
[0126] (1) Preparation of composite solder:
[0127] A) The raw materials of the Ti(C,N)-based metal ceramic intermediate layer and the Ti-Zr-Cu-Ni layer are mixed evenly with polyethylene glycol (PEG6000) to obtain slurries of each layer; the mass of the polyethylene glycol is 5% of the mass of the slurry;
[0128] B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body at a pressure of 150 MPa;
[0129] C) vacuum sintering the green body to obtain a composite brazing material; the sintering temperature is 1440°C and the sintering time is 1h;
[0130] (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod;
[0131] (3) At a temperature of 900°C and a vacuum of 2.0×10 -3 Vacuum brazing is performed under 400 Pa to obtain the ceramic brazing vacuum electrical connector.
[0132] The particle sizes and oxygen contents of the raw materials used in the composite solders in the above-mentioned embodiments and comparative examples are shown in Table 1.
[0133] Table 1: Raw material properties of composite solder
[0134]
[0135] The shear properties of the solder joints of the ceramic brazed vacuum electrical connectors prepared in the above embodiments and comparative examples were tested using a WDW-100 universal tensile testing machine. The results are shown in Table 2.
[0136] Table 2: Shear performance test results
[0137]
[0138] As can be seen from Table 2, the shear strength of the solder joint after brazing with the composite solder of the present invention in Examples 1 to 3 can reach more than 200 MPa. In Comparative Example 1, only Ti-Zr-Cu-Ni solder is used to braze the ceramic insulator with the metal core rod and the vacuum flange, lacking the transition of the Ti(C, N)-based metal ceramic layer, and the shear strength of the solder joint is significantly reduced compared with the embodiment. In the composite solder of Comparative Example 2, no Ti-Zr-Cu-Ni layer is provided, and the Ti-Ni layer is used as the surface layer to braze the ceramic insulator with the metal core rod and the vacuum flange. The wetting and spreading performance of the solder on the surface of the ceramic insulator is reduced, and the shear strength of the solder joint is also reduced compared with the embodiment. In the composite solder of Comparative Example 3, no Ti-Ni transition layer is provided between the Ti(C, N)-based metal ceramic layer and the Ti-Zr-Cu-Ni layer. The diffusion and flow of elements such as Zr and Cu during the sintering process will have an adverse effect on the performance of the Ti(C, N)-based metal ceramic layer, resulting in a decrease in the shear strength of the solder joint. It is shown that brazing with the composite solder of the present invention can significantly improve the mechanical properties of the vacuum electrical connector, which is beneficial to high-strength plug-in connection.
[0139] At the same time, the vacuum electrical connector helium mass spectrometer leak detector prepared in the present invention has a leak rate of ≤5×10 -11 Pa·m 3 / s; at room temperature and pressure, the insulation resistance between the metal core rod and the CF flange is ≥1000MΩ; between the metal core rod and the CF flange, the test voltage is 3000V (AC effective value, 50Hz), acting for 1 minute, there is no breakdown and arcing phenomenon, and the leakage current does not exceed 1mA; it has good sealing performance and electrical performance.
[0140] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A ceramic brazing vacuum electrical connector, characterized in that: It comprises a metal core rod, a ceramic insulating part and a vacuum flange sleeved outside the metal core rod; one end of the ceramic insulating part is welded to the metal core rod through a composite brazing material, and the other end is welded to the vacuum flange through a composite brazing material; there is a clearance fit between the vacuum flange and the metal core rod; The composite brazing material is made by pressing and sintering five layers of materials, including a Ti(C, N)-based metal ceramic middle layer, a Ti-Ni transition layer arranged on both sides of the Ti(C, N)-based metal ceramic middle layer, and a Ti-Zr-Cu-Ni layer arranged outside the Ti-Ni transition layers on both sides; The raw materials of the Ti(C,N)-based metal ceramic intermediate layer include TiC powder, TiN powder, Mo2C powder, nickel powder, molybdenum powder and carbon powder in a mass ratio of 30-50:10:5-10:30-35:15-20:1-2; The raw materials of the Ti-Ni transition layer include nickel powder and titanium powder in a mass ratio of 50-70:50-30; The raw materials of the Ti-Zr-Cu-Ni layer include titanium powder, zirconium powder, copper powder and nickel powder in a mass ratio of 55-60:10-15:15:15-25.
2. The ceramic brazing vacuum electrical connector according to claim 1, characterized in that: The particle size of nickel powder, titanium powder, molybdenum powder, zirconium powder, copper powder and carbon powder is 2~5μm; the particle size of TiC powder, TiN powder and Mo2C powder is 0.5~1μm.
3. The ceramic brazing vacuum electrical connector according to claim 1 or 2, characterized in that: The thickness of the Ti(C,N)-based metal ceramic intermediate layer in the composite solder is 200~500μm, the thickness of the two Ti-Ni transition layers is 20~50μm, and the thickness of the two Ti-Zr-Cu-Ni layers is 100~200μm.
4. The ceramic brazing vacuum electrical connector according to claim 1, characterized in that: The ceramic insulating member is one of Al2O3 ceramic, SiC ceramic and Si3N4 ceramic.
5. The ceramic brazing vacuum electrical connector according to claim 1 or 4, characterized in that: The metal core rod is one of copper and its alloy, stainless steel, aluminum and its alloy.
6. A method for preparing a ceramic brazed vacuum electrical connector according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of composite solder: A) respectively mixing the raw materials of the Ti(C,N)-based metal ceramic intermediate layer, the Ti-Ni transition layer and the Ti-Zr-Cu-Ni layer with a forming agent to obtain slurries of each layer; B) sequentially coating the inner surface of the mold with a Ti-Zr-Cu-Ni layer slurry, a Ti-Ni transition layer slurry, a Ti(C,N)-based metal ceramic intermediate layer slurry, a Ti-Ni transition layer slurry, and a Ti-Zr-Cu-Ni layer slurry, and then pressing the mold into a green body; C) vacuum sintering the green body to obtain a composite brazing material; (2) Assembling the ceramic insulating member and the vacuum flange with the metal core rod, and placing the composite brazing material at the welding position between the ceramic insulating member and the vacuum flange and the metal core rod; (3) After vacuum brazing, the ceramic brazed vacuum electrical connector is obtained.
7. The preparation method according to claim 6, characterized in that: The molding agent described in step A) is selected from one of polyethylene glycol, liquid paraffin, polyvinyl alcohol and glycerol; the mass of the molding agent is 5-10% of the mass of the slurry.
8. The preparation method according to claim 6, characterized in that: The pressure during pressing in step B) is 100-200 MPa.
9. The preparation method according to claim 6, characterized in that: The sintering temperature in step C) is 1400-1500°C, and the sintering time is 1-2 hours.
10. The preparation method according to claim 6, characterized in that: The temperature during vacuum brazing in step (3) is 850-950°C and the vacuum degree is 8.0×10 -3 Below Pa.
Citation Information
Patent Citations
Ceramic brazing connector and preparation method thereof
CN117199888A
Brazing material and preparation method thereof as well as brazing method using the material
CN101327551A
Brazing and casting process of metal ceramic composite lining board
CN102554385A